La prueba judicial: una aproximación realista (2017)
The issue of the veracity of legal claims and its consequences is based, first and foremost, on the study of legal philosophy. This article explores the substantivity of judicial evidence from the perspective of classical legal realism, as a key mechanism against claims of truth and the different models of truth from different positions. Judicial decisions go through ontological and definitive interpretations of what is fair and right, in relation to judicial evidence, through the exercise of legal science by the jurist.